113 Long Term Outcomes of Patients with Type 2 Myocardial Infarction or Myocardial Injury. (3rd June 2016) - Chapman, Andrew R; Shah, Anoop SV; Anand, Atul; Strachan, Fiona; McAllister, David; Newby, David; Mills, Nicholas
Abstract : Background: Type 2 myocardial infarction is defined as myocardial necrosis due to an imbalance in oxygen supply or demand, and is differentiated from myocardial injury by the presence of symptoms or signs of myocardial ischaemia. Both may occur in a wide range of cardiac and non-cardiac conditions and the long term consequences are uncertain. Methods: We identified all consecutive patients (n = 2, 122) presenting to a tertiary cardiac centre with cardiac troponin I concentrations above the diagnostic threshold of 50 ng/L irrespective of presenting complaint. Two cardiologists independently adjudicated the diagnosis of type 1 myocardial infarction, type 2 myocardial infarction or myocardial injury. The primary outcome was all-cause mortality. Secondary outcomes included subsequent hospitalisation for type 1 myocardial infarction, and cardiovascular or non-cardiovascular mortality. Incidence rates for primary and secondary outcomes were derived for patients stratified by the index diagnosis and cox proportional hazard models constructed to estimate risk of death or hospitalisation, adjusting for age and sex. Results: The adjudicated diagnosis was type 1 myocardial infarction in 1, 171 patients (55.2%), type 2 myocardial infarction in 429 patients (20.2%) and myocardial injury in 522 patients (24.6%; Table 1). During 8, 809 patient years follow up there were 1, 231 deaths (552 cardiovascular, 623 non-cardiovascular; Figure 1) and 307 patients were hospitalised for type 1 myocardial infarction. Patients with type 2 myocardial infarction were at higher risk of all-cause mortality compared to those with type 1 myocardial infarction (20.9 vs 8.7 events per 100 person years; hazard ratio [HR] 1.58, 95% CI 1.37–1.82), but were at lower risk of subsequent hospitalisation for type 1 myocardial infarction (3.2 vs 4.3 events per 100 person years; HR 0.53, 95% CI 0.38–0.73). Survival in patients with myocardial injury was worse, even compared to those with type 2 myocardial infarction (27.6 vs 20.9 events per 100 person years; HR 1.17, 95% CI 1.01–1.36). Conclusions: Patients with type 2 myocardial infarction and myocardial injury have a very poor prognosis compared to those with type 1 myocardial infarction. Whether worse outcomes are due to the presence of treatable cardiovascular disease or as a consequence of other co-morbid conditions requires further investigation.